USING REMOTE-SENSING TO IDENTIFY WINTERING AND MOULTING AREAS OF A LONG-DISTANCE MIGRANT: MARSH WARBLER (ACROCEPHALUS PALUSTRIS) - Miholcsa, T; Harnos, A; Csorgo, T (Applied ecology and environmental research, 2016)
Ecological conditions in wintering quarters strongly influence the survival of long-distance migrant species, moreover food abundance and quality in moulting areas determine feather growth rate and wing length too. These circumstances via net primary production can be well characterized by the Normalized Difference Vegetation Indices (NDVI) of the respective areas. In this paper we approach this subject from the opposite direction: supposing this strong relationship between vegetation indices and survival, respectively moult, we try to identify putative wintering and moulting areas of Marsh Warblers (Acrocephalus palustris) with the help of Spearman's rank correlations between annual survival indices, wing lengths and NDVI from entire Africa. We have chosen this species because its movements, stop-over sites and wintering areas are relatively well known compared to other trans-Saharan migrants, hence with the help of the literature we can test the validity of our results. In lack of sufficient ringing-recapture data we have applied a new survival index which is based on the ratio of the abundances of different age classes. Our results are consistent with the available information from literature showing that our survival index, wing lengths and our methods are appropriate to search for putative wintering and/or moulting areas.